Proceedings of the 2013 ACM Symposium on Principles of Distributed Computing 2013
DOI: 10.1145/2484239.2484256
|View full text |Cite
|
Sign up to set email alerts
|

Byzantine vector consensus in complete graphs

Abstract: Consider a network of n processes each of which has a d-dimensional vector of reals as its input. Each process can communicate directly with all the processes in the system; thus the communication network is a complete graph. All the communication channels are reliable and FIFO (first-in-first-out). The problem of Byzantine vector consensus (BVC) requires agreement on a d-dimensional vector that is in the convex hull of the d-dimensional input vectors at the non-faulty processes. We obtain the following result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
88
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(91 citation statements)
references
References 23 publications
3
88
0
Order By: Relevance
“…Considering Byzantine failures and asynchronous message-passing systems, ǫ-approximate agreement has very recently been generalized to the case where the proposed values are points in an m-dimensional space R m [26,33]. A decided value (point) must then belong to the convex hull of the points proposed by the non-faulty processes (validity), and the Euclidean distance between any pair of values -points -decided by non-faulty processes has to be upper bounded by a predefined constant.…”
Section: B2 Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering Byzantine failures and asynchronous message-passing systems, ǫ-approximate agreement has very recently been generalized to the case where the proposed values are points in an m-dimensional space R m [26,33]. A decided value (point) must then belong to the convex hull of the points proposed by the non-faulty processes (validity), and the Euclidean distance between any pair of values -points -decided by non-faulty processes has to be upper bounded by a predefined constant.…”
Section: B2 Related Workmentioning
confidence: 99%
“…Thus, (1, ǫ)-solo approximate agreement problem in R m is essentially the problem that has been recently considered in the context of t Byzantine failures and asynchronous message-passing systems [26,33], where it is shown that it can be solved iff n > t(m + 2).…”
Section: Introductionmentioning
confidence: 99%
“…Due to this correspondence, we use the terms point and vector interchangeably. Recent work [9,12] has addressed Byzantine vector consensus, and presented algorithms with optimal fault tolerance in complete graphs. The correctness conditions for Byzantine vector consensus (elaborated below) cannot be satisfied by independently performing consensus on each element of the input vectors; therefore, new algorithms are necessary [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…The input vector at each process may also be viewed as a point in the d-dimensional Euclidean space R d , where d > 0 is a finite integer. Recent work [9,12] has addressed Byzantine vector consensus, and presented algorithms with optimal fault tolerance in complete graphs. This paper considers Byzantine vector consensus in incomplete graphs using a restricted class of iterative algorithms that maintain only a small amount of memory across iterations.…”
mentioning
confidence: 99%
“…A widely studied model of consensus under attack is the byzantine consensus problem [18], [19], [20], in which a number of processors have to agree on a value even if some processors may report a false value to influence the consensus. In our work the processors are the regions, but the attack is fundamentally different; its goal is to impede the convergence of the distributed state estimation, and the mitigation scheme we propose not only provides convergence but it also allows to localize the attack.…”
Section: Related Workmentioning
confidence: 99%